A rare presentation of bilateral synchronous renal tumours misdiagnosed as tuberculosis - Debi M. Moagi; Busiswa F. Bisiwe (South African Journal of Oncology)
A 32-year-old woman with dialysis-requiring kidney failure presented with constitutional symptoms and bilateral kidney masses and was initially diagnosed with renal tuberculosis (TB). However, despite TB treatment, her condition deteriorated, leading to a right nephrectomy. Histopathological examination revealed the presence of embryonal rhabdomyosarcoma (ERMS), a rare malignancy typically seen in paediatric populations. Alternative diagnoses, even rare ones like ERMS, should be considered when dealing with bilateral kidney masses. Radical nephrectomy remains the primary treatment for ERMS, but adjuvant therapies may also be beneficial.